Pengaruh Profesionalisme Guru Terhadap Peningkatan Prestasi Belajar Siswa Kelas X Di Madrasah Aliyah Muhammadiyah 02 Pondok Modern Paciran Lamongan - Himmatul Husniyah; Hilal Husni; Chandra Agustian (STIT Muhammadiyah Paciran, 2022)
This study aims to identify teacher professionalism towards the improvement of student achievement in class X at Madrasah Aliyah Muhammadiyah 02 Pondok Modern PaciranLamongan. The hypothesis proposed is